Efektifitas Pegawai Dinas Pendidikan Dan Kebudayaan Dalam Pemberantasan Buta Aksara Di Desa Labengki Kecamatan Lasolo Kabupaten Konawe Utara - Ningsih, Reschy Yunita; Aminuddin, Aminuddin; Taufik, Taufik (REZ PUBLICA, 2021)
The purpose of this study was to determine the effectiveness of the Office of Education and Culture Employees in the Eradication of Illiteracy in Labengki Village, Lasolo District, Konawe Utara Regency. The research method used was a qualitative method. The results obtained were the Illiteracy Eradication in Lebengki Village, Lasolo District, Konawe Regency. The North is still effective where the level of illiteracy has not decreased, namely in 2017 as many as 83 people, then in 2018 as many as 86 people and then in 2019 there were 88 people. This is a form of effective illiteracy in Labengki Village, Lasolo District, Regency Konawe Utara, in this case the dimension that is still lacking in handling is the number of results achieved.